The synthesis of galactose-containing amphiphiles - Е. А. Ivanova; N. G. Morozova; М. М. Maslov; G. A. Serebrennikova (Тонкие химические технологии, 2010)
The synthesis of galactose-containing amphiphiles based on tetradecanol, cholesterol or 1,2-di-O-tetradecylglycerol has been described. The compounds synthesized can be used as components of liposomal targeted carries for therapeutics delivery into liver cells.